HUBUNGAN ANTARA PENDEKATAN PEMBELAJARAN PEER GROUP DENGAN HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI SMA NEGERI 1 PALEMBANG - Lismawati Lismawati; Syarwani Ahmad; Neta Dian Lestari (UNIVERSITAS MUHAMMADIYAH METRO, 2019)
The purpose of the study was to determine whether there is a relationship between the peer group learning approach and student learning outcomes. The method used in this research is the Correlational Quantitative method. The research sample amounted to 53 students consisting of two classes namely class XI IPS 4 totaling 32 students and XI IPS 5 totaling 21 students. The technique of collecting data in this study uses observation techniques, questionnaires, and documentation. The results showed that the average relationship between the peer group learning approach in learning activities gained an average of 72.88 with the tifKtif 'criterion while the student learning outcomes obtained the criteria of